A low-carbon and hunger-free future for Bangladesh: An ex- ante assessment of synergies and trade-offs in different transition pathways - Moghayer, Saeed; Zurek, Monika; Muzammil, Maliha; Mason-D’Croz, Daniel; Magrath, John; Tabeau, Andrzej; Vervoort, Joost Mattheus; Achterbosch, Thom (Frontiers in Environmental Science, 2023)
Feeding and nourishing a growing global population in Bangladesh is a major challenge under a changing climate. To support decision makers to develop scenario-guided enabling policy for food security in futures under climate change, a multi-level participatory scenario approach with corresponding modelling and decision support tools are developed and applied. The results presented in this paper show how under different scenarios, agri-food system may transform in the next decade as a result of the interaction of intertwined institutional, technological, and market drivers in Bangladesh. For scenario building, the food and agriculture community were brought together with the climate and energy community. We also experimented with different ways to bring voices that are often less included in the policy making such as poor rural communities and youth. The scenario quantification is performed by MAGNET, a GTAP-based multi-sector and multi-region Computable General Equilibrium model. The simulation results depict a comprehensive picture of corresponding and varied pressures on agricultural resources as well as opportunities for economic development and trade in Bangladesh. Finally we so an ex-ante assessment of the trade-offs and synergies between zero-hunger and zero-emission related targets within Bangladesh Sustainable Development Goals (SDGs) under the developed scenarios.